2018
DOI: 10.3389/fcimb.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Gametocytes of the Malaria Parasite Plasmodium falciparum Interact With and Stimulate Bone Marrow Mesenchymal Cells to Secrete Angiogenetic Factors

Abstract: The gametocytes of Plasmodium falciparum, responsible for the transmission of this malaria parasite from humans to mosquitoes, accumulate and mature preferentially in the human bone marrow. In the 10 day long sexual development of P. falciparum, the immature gametocytes reach and localize in the extravascular compartment of this organ, in contact with several bone marrow stroma cell types, prior to traversing the endothelial lining and re-entering in circulation at maturity. To investigate the host parasite in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…Given the shared binding phenotype to human bone marrow MSCs, it is most likely that such shared antigens are also involved in iRBC interactions in the extravascular bone marrow niche. Interestingly, the presence of parasite antigens on the gametocyte iRBC surface is limited to stages I and II, after which the antigens are gradually removed by as yet unknown processes 77 , coinciding with the observed loss of binding 74 . Invasion assays with P. falciparum and P. berghei have demonstrated that the earliest RBC precursor stage that can be invaded and support parasite growth is the orthochromatic erythroblast 51,60,80 , in the final 48-72 h of erythropoiesis.…”
Section: Box 1 | Evolution Of a Haematopoietic Reservoir In Plasmodiumentioning
confidence: 90%
See 1 more Smart Citation
“…Given the shared binding phenotype to human bone marrow MSCs, it is most likely that such shared antigens are also involved in iRBC interactions in the extravascular bone marrow niche. Interestingly, the presence of parasite antigens on the gametocyte iRBC surface is limited to stages I and II, after which the antigens are gradually removed by as yet unknown processes 77 , coinciding with the observed loss of binding 74 . Invasion assays with P. falciparum and P. berghei have demonstrated that the earliest RBC precursor stage that can be invaded and support parasite growth is the orthochromatic erythroblast 51,60,80 , in the final 48-72 h of erythropoiesis.…”
Section: Box 1 | Evolution Of a Haematopoietic Reservoir In Plasmodiumentioning
confidence: 90%
“…Interestingly, a recent study reported the binding of both asexual stages and immature P. falciparum gametocytes to human bone marrow mesenchymal stem cells (MSCs) in a 3D culture system. This binding was trypsin-sensitive, but independent of PfEMP1 and ICAM1, yet the receptor for the interaction could not be identified 74 . In a separate study, no binding to RBC precursor cells was observed 75 .…”
Section: Box 1 | Evolution Of a Haematopoietic Reservoir In Plasmodiumentioning
confidence: 91%
“…Only in the last decade has Plasmodium transmission biology research re‐gained great momentum, leading to a large number of questions regarding Plasmodium interactions in the bone marrow, including mechanisms of extravasation, development and egress (Aguilar et al, ; Aingaran et al, ; Farfour et al, ; Joice et al, ; Lavazec, ; Lavazec et al, ; Lavazec & Alano, ; Messina et al, ; Naissant et al, ; Neveu et al, ; Ramdani et al, ; Rogers et al, ). Beyond P. falciparum , the bone marrow has been shown to be an important niche for P. vivax development, including gametocyte maturation and asexual development responsible for chronicity (Baro et al, ; Markus, ; Mayor & Alano, ; Obaldia et al, ).…”
Section: Primary Lymphoid Organs In Parasitic Infectionsmentioning
confidence: 99%
“…However, histology techniques combined with human and animal autopsies have shown that the bone marrow can influence pathology related to parasitic infections and in some cases, is even a key niche for parasite development. Direct and indirect bone marrow involvement in pathology has been suggested for parasites including Plasmodium spp., (Alano, 2017;Baro et al, 2017;De Niz et al, 2018;Duffier et al, 2016;Farfour et al 2012;Joice et al, 2014;Lee et al, 2017;Lee et al, 2018;Mayor & Alano, 2015;Messina et al, 2018;Neveu et al, 2018;Rogers et al, 2000;Smalley et al 1981;Waseem et al, 2016;Wickramasinghe et al, 1987), Toxoplasma gondii (Brouland et al, 1996), Leishmania spp., (Ali & Hussain, 2014;Hellal & Kundu, 2013;Kumar et al, 2007), Schistosoma spp., (Azevedo et al, 2015;Jones & Leday, 2014;Kamal et al 1989) and Trypanosoma spp. (Baena Terán et al, 2012;Bockstal, Guirnalda, et al, 2011;Bockstal, Geurts, & Magez, 2011;Carbajosa et al, 2017;De Diego et al 1998;Felizardo et al, 2018;Habila et al, 2014;Mabbott & Sternberg, 1995;Müller et al, 2018;Obishakin et al 2014;Souza et al, 2014;Stijlemans et al, 2016).…”
Section: Biological Relevance Of the Bone Marrowmentioning
confidence: 99%
See 1 more Smart Citation